Effect of three organic fertilizers treatments on sensory evaluations of baby spinach (Spinacia oleracea L.) - Parwada, C.; Chigiya, V.; Ngezimana, W.; Chipomho, J. (International Journal of Horticultural Science, 2021)
Sources of fertilizer are one of the major factors influencing baby spinach leaf texture, sweetness, bitterness and after-taste. However, the effects of fertilizer sources on baby spinach growth performance and consumer preferences are not known. A survey was carried out at the Seke Teachers’ College (SKC) community, Zimbabwe to determine the consumer preferences on the baby spinach grown on the organic fertilizer (cattle, poultry and goat manures) as well as on control inorganic  fertilizers (7% N, 14% P, 7% K). The study used 32 females and 30 males as panellists for sensory evaluations. Organoleptic tests were performed for the baby spinach leaves using a panel of 62 testers. An interval line scale (16 cm long) was used to measure the liking for sweetness, colour, bitterness and after-taste. A 9-point hedonic scale was used to decide the overall preferences. Organoleptic tests showed significant differences (P